Corporate Social Responsibility scepticism and its influence on consumers’ purchasing intentions - Bitterolf, Maxime (2017)
Corporate Social Responsibility (CSR) has become mainstream as an increasing number of companies use this practice. At the same time, as some CSR related scandals occurred, consumers became more sceptical towards CSR engaged firms. This study is motivated by one research question and two sub-questions: (1) how CSR scepticism influences purchasing intentions? (a) Which factors could trigger CSR scepticism for consumers, (b) What impact does greenwashing have on consumers and what do they associate to it? Primary data were collected through 20 in-depth semi-structured interviews and were analysed thanks to thematic coding techniques which helped to build hypotheses. The findings from this research suggested that interviewees were generally sceptical towards CSR initiatives and were reluctant to pay more for socially and environmentally-engaged products. Despite price concerns, other influencing factors such as trust, product quality, transparency and brand reputation seemed to influence consumers’ scepticism and purchasing intentions. Moreover, regarding greenwashing, interesting results were found as interviewees strongly condemned this practice and sometimes wrongly identified it with CSR. Because of greenwashing, interviewees argued that they would boycott products as a response to the lies and misleading practices engaged by firms. Some recommendations could be given for companies wishing to implement CSR activities. First, firms should communicate more about the initiative, in order to provide more transparency about the programmes they fund. Secondly, the initiative should not be implemented just to improve brand image and firm reputation like in Tobacco and oil industries. The initiative should be frank, public-oriented and not serving firm motives only.